C.1 - Haldea, Gajendra (New Delhi, 2011)
This book is a rare insider view of infrastructure sector reforms-where India is, where it should be, and what is stopping it from getting there. It offers a nuanced portrayal of the processes involved at different stages, from conception to implementation, of diverse infrastructure projects-roads, railways, ports, airports, telecom, and power. From policy cobwebs to manoeuvring and rent-seeking, it tells all. It also brings out the half-full glass that offers lessons for the future. The author recounts his experience of structuring and negotiating recent mega infrastructure projects and of drafting laws, documents, and policies that laid the foundation for private participation in infrastructure. In the process, he critiques the corruption, vested interests, and crony capitalism in the infrastructure sector, and argues that current bottlenecks can only be removed through good governance and reforms in the sector. Weaving together the political, institutional, and economic, this volume illustrates the complexities involved in the provision of infrastructure and outlines strategies for future development.
Keywords: Economic development-India